Black aluminum oxide ceramic material as well as preparation method and application thereof
Through vacuum pressure-free sintering technology, the problem of insufficient thermal conductivity and density of black alumina ceramic materials is solved, and high density and high thermal conductivity ceramic materials are achieved, which are suitable for efficient heat dissipation and temperature control of semiconductor devices.
Patent Information
- Application Number
- CN202411728694.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The thermal conductivity and density of existing black alumina ceramic materials are insufficient, making it difficult to meet the needs of semiconductor devices for efficient heat dissipation and temperature control.
Vacuum pressure-free sintering technology is adopted to suppress the growth of grain size by sintering under low air pressure, effectively discharge gas in the blank, and improve the density and thermal conductivity of ceramic materials.
The density and thermal conductivity of black alumina ceramic materials have been significantly improved, with density up to 99.1g/cm3 and thermal conductivity up to 32W/m.k, meeting the needs of semiconductor devices for efficient heat dissipation and temperature control.
Smart Images

Figure BDA0005159790520000071 
Figure BDA0005159790520000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials and relates to a black alumina ceramic material and a preparation method and application thereof. Background Art
[0002] With the development and growth of the semiconductor industry, alumina ceramics also have broad space in the field of semiconductor packaging. Among them, black alumina ceramics have a series of superior properties such as light shielding, good air tightness, strong radiation resistance, wear resistance, high temperature resistance, good insulation, acid and alkali resistance, etc., so they have broad market prospects and development space.
[0003] Semiconductor devices must not only have high density and light protection, but also have a certain thermal conductivity. Taking dry etching as an example, the temperature control of the wafer is crucial in the semiconductor process. The wafer needs to be controlled at a specific temperature of 100°C to -70°C to maintain a certain etching characteristic. Therefore, the wafer needs to be heated or dissipated through alumina ceramics to accurately control the wafer temperature. When preparing alumina ceramics, a certain proportion of binder is often added to make it shape, but in actual sintering, the volatilization of the binder will leave more gaps, which cannot be discharged during the sintering process. The presence of more gaps will reduce the thermal conductivity of alumina ceramics, which is not conducive to heat dissipation.
[0004] CN107954698A discloses a black alumina with high ceramic performance and a preparation method thereof. The method adjusts the ratio of a sintering aid and a pigment in the alumina ceramic, and sintering is performed at 1620°C in a high-temperature kiln to obtain black alumina with good toughness and wear resistance.
[0005] CN117843350A discloses a black alumina ceramic and a preparation method thereof. The black alumina ceramic prepared by adjusting a specific ratio has a low sintering temperature below 1500°C, and the four-point bending strength can reach above 425MPa.
[0006] The above scheme mainly changes the composition ratio of sintering aid and pigment in alumina ceramics and adopts traditional pressureless sintering technology to prepare light-shielding black alumina ceramics, but the thermal conductivity and density of alumina ceramics still need to be improved. Summary of the invention
[0007] The purpose of the present invention is to provide a black alumina ceramic material and a preparation method and application thereof. The black alumina ceramic material prepared by the method of the present invention has smaller grains, smaller pores and higher density, and has higher compactness and thermal conductivity.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a black alumina ceramic material, the preparation method comprising the following steps:
[0010] (1) mixing aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide, chromium oxide and a solvent to obtain an aluminum oxide ceramic mixed solution;
[0011] (2) mixing the alumina ceramic mixed liquid with a binder, and grinding to obtain an alumina ceramic powder;
[0012] (3) The alumina ceramic powder is subjected to cold pressing treatment and then to vacuum pressureless sintering treatment to obtain the black alumina ceramic material.
[0013] In the preparation process of the black alumina ceramic material of the present invention, vacuum pressureless sintering is adopted to sinter the sample under low pressure. Compared with ordinary solid phase sintering, vacuum pressureless sintering can not only inhibit the growth of grain size but also effectively discharge the gas in the green body under a longer holding time, thereby improving the density and thermal conductivity of the black alumina ceramic.
[0014] Preferably, the mass ratio of aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in step (1) is (85-90):(0.5-2):(2-4):(2-4):(2-5):(5-10), for example: 85:2:3:3:2:5, 88:1:2:2:2:5, 86:1:2:3:2:6, 87.5:0.5:2:2:3:5 or 85:2:2:2:3:6, etc., is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, the solvent in step (1) comprises water.
[0016] Preferably, the mixing in step (1) comprises pre-mixing magnesium oxide, silicon dioxide, iron oxide, manganese oxide, chromium oxide and a solvent in one step, and then adding aluminum oxide for two-step mixing.
[0017] Preferably, the one-step mixing time is 2 h to 4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0018] Preferably, the two-step mixing time is 10 h to 20 h, for example, 10 h, 12 h, 15 h, 18 h or 20 h, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the solid content of the alumina ceramic mixed solution in step (1) is 50% to 60%, for example: 50%, 52%, 55%, 58% or 60%, etc.
[0020] Preferably, the binder in step (2) comprises a polyvinyl alcohol aqueous solution, i.e., a PVA solution.
[0021] Preferably, the mass concentration of the polyvinyl alcohol aqueous solution is 3% to 8%, for example, 3%, 4%, 5%, 7% or 8%, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, the mass ratio of the solute in the polyvinyl alcohol aqueous solution to the solid material in the alumina ceramic mixed solution is (0.2-1):100, for example: 0.2:100, 0.4:100, 0.6:100, 0.8:100 or 1:100, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, after the grinding treatment in step (3), the obtained material is introduced into an aluminum pan for drying.
[0024] Preferably, the pressure of the cold pressing treatment in step (3) is 150 MPa to 300 MPa, for example, 150 MPa, 180 MPa, 200 MPa, 250 MPa or 300 MPa, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the holding time of the cold pressing treatment in step (3) is 2 min to 5 min, for example, 2 min, 2.5 min, 3 min, 4 min or 5 min, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the cold pressing treatment in step (3) is followed by a degreasing treatment.
[0027] Preferably, the vacuum degree of the vacuum pressureless sintering process in step (3) is ≤3×10 -3 Pa.
[0028] Preferably, the heating rate of the vacuum pressureless sintering treatment in step (3) is 0.5°C / min to 2°C / min, for example, 0.5°C / min, 0.8°C / min, 1°C / min, 1.5°C / min or 2°C / min, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] Preferably, the temperature of the vacuum pressureless sintering treatment in step (3) is 1500°C to 1600°C, for example: 1500°C, 1520°C, 1550°C, 1580°C or 1600°C, etc., not limited to the listed values, other values not listed within the numerical range are also applicable.
[0030] Preferably, the holding time of the vacuum pressureless sintering treatment in step (3) is 4 h to 6 h, for example 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] In a second aspect, the present invention provides a black alumina ceramic material, which is prepared by the preparation method described in the first aspect.
[0032] In a third aspect, the present invention provides an application of the black alumina ceramic material as described in the second aspect, wherein the black alumina ceramic material is used in semiconductor devices.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention adopts a vacuum pressureless sintering method to sinter the sample under low pressure, thereby inhibiting the growth of grain size, effectively discharging the gas in the body, and improving the density and thermal conductivity of the alumina ceramic.
[0035] (2) The black alumina ceramic material prepared by the method of the present invention has smaller grains, smaller pores and higher density, and has higher compactness and thermal conductivity.
[0036] (3) The density of the black alumina ceramic material of the present invention can reach 96.8 g / cm 3 The thermal conductivity can reach above 22W / mk. By adjusting the preparation conditions, the density of the black alumina ceramic material can reach 99.1g / cm 3 Above, the thermal conductivity can reach above 32W / mk. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0038] Example 1
[0039] This embodiment provides a black alumina ceramic material, and the black alumina ceramic material is prepared by the following method:
[0040] (1) weighing aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in a mass ratio of 88:1:2:2:2:5, first placing magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in pure water, premixing for 3 hours, then adding aluminum oxide and mixing for another 15 hours to obtain an aluminum oxide ceramic mixed solution with a solid content of 55%;
[0041] (2) adding a 5% PVA solution to an alumina ceramic mixed solution for ball milling, wherein the mass ratio of the solute in the PVA solution to the solid material in the alumina ceramic mixed solution is 0.5:100, and after the ball milling is completed, the slurry is introduced into an aluminum pan for drying to obtain a uniformly mixed alumina ceramic powder;
[0042] (3) The uniformly mixed alumina ceramic powder is placed in a rubber sleeve and cold isostatically pressed at a pressure of 200 MPa for a holding time of 3 min. The cold pressed green body is first placed in a muffle furnace for degreasing, and the degreased alumina green body is placed in a vacuum pressureless sintering furnace and vacuumed to ≤3×10 -3 Pa, start heating, control the heating rate to be 1°C / min, the highest temperature to be 1550°C, and keep warm for 5h to obtain the black alumina ceramic material.
[0043] Example 2
[0044] This embodiment provides a black alumina ceramic material, and the black alumina ceramic material is prepared by the following method:
[0045] (1) weighing aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in a mass ratio of 85:2:3:3:2:5, first placing magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in pure water, premixing for 2 hours, then adding aluminum oxide and mixing for another 10 hours to obtain an aluminum oxide ceramic mixed solution with a solid content of 50%;
[0046] (2) adding a 3% PVA solution to an alumina ceramic mixture for ball milling, wherein the mass ratio of the solute in the PVA solution to the solid material in the alumina ceramic mixture is 0.2:100, and after the ball milling is completed, the slurry is introduced into an aluminum pan for drying to obtain a uniformly mixed alumina ceramic powder;
[0047] (3) The uniformly mixed alumina ceramic powder is placed in a rubber sleeve and cold isostatically pressed at a pressure of 150 MPa for a holding time of 5 min. The cold pressed green body is first placed in a muffle furnace for degreasing, and the degreased alumina green body is placed in a vacuum pressureless sintering furnace and vacuumed to ≤3×10 -3 Pa, start heating, control the heating rate to be 1°C / min, the maximum temperature to be 1500°C, and keep warm for 6 hours to obtain the black alumina ceramic material.
[0048] Example 3
[0049] This embodiment provides a black alumina ceramic material, and the black alumina ceramic material is prepared by the following method:
[0050] (1) weighing aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in a mass ratio of 85:2:2:2:3:6, first placing magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in pure water, premixing for 2 hours, then adding aluminum oxide and mixing for another 20 hours to obtain an aluminum oxide ceramic mixed solution with a solid content of 60%;
[0051] (2) adding a PVA solution with a mass concentration of 8% to an alumina ceramic mixed solution for ball milling, wherein the mass ratio of the solute in the PVA solution to the solid material in the alumina ceramic mixed solution is 1:100, and after the ball milling is completed, the slurry is introduced into an aluminum pan for drying to obtain a uniformly mixed alumina ceramic powder;
[0052] (3) The uniformly mixed alumina ceramic powder is placed in a rubber sleeve and cold isostatically pressed at a pressure of 300 MPa for a holding time of 2 min. The cold pressed green body is first placed in a muffle furnace for degreasing, and the degreased alumina green body is placed in a vacuum pressureless sintering furnace and vacuumed to ≤3×10 -3 Pa, start heating, control the heating rate to be 2°C / min, the maximum temperature to be 1600°C, and keep warm for 4h to obtain the black alumina ceramic material.
[0053] Example 4
[0054] The only difference between this embodiment and embodiment 1 is that the temperature of vacuum pressureless sintering is 1400° C., and other conditions and parameters are exactly the same as those in embodiment 1.
[0055] Example 5
[0056] The only difference between this embodiment and embodiment 1 is that the temperature of vacuum pressureless sintering is 1700° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0057] Example 6
[0058] The only difference between this embodiment and embodiment 1 is that the holding time of vacuum pressureless sintering is 2 hours, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0059] Example 7
[0060] The only difference between this embodiment and embodiment 1 is that the holding time of vacuum pressureless sintering is 8 hours, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0061] Comparative Example 1
[0062] The only difference between this comparative example and Example 1 is that no vacuum is drawn during the sintering process, and only conventional pressureless sintering is performed. Other conditions and parameters are exactly the same as those in Example 1.
[0063] Performance Test:
[0064] The thermal conductivity of the alumina electrostatic chuck provided in the above-mentioned embodiment and comparative example was tested by using a hotdisk thermal constant analyzer, and the density was tested according to the Archimedes drainage method; the test results are shown in Table 1:
[0065] Table 1
[0066]
[0067]
[0068] As can be seen from Table 1, from Examples 1-7, the density of the black alumina ceramic material of the present invention can reach 96.8 g / cm 3 The thermal conductivity can reach above 22W / mk. By adjusting the preparation conditions, the density of the black alumina ceramic material can reach 99.1g / cm 3 Above, the thermal conductivity can reach above 32W / mk.
[0069] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the black alumina ceramic material of the present invention, the temperature of vacuum pressureless sintering will affect its performance. When the temperature of vacuum pressureless sintering is controlled at 1500-1600°C, the performance of the obtained black alumina ceramic material is better. If the temperature of vacuum pressureless sintering is too high, the density of the black alumina ceramic material will increase slightly, but the thermal conductivity will decrease. If the temperature of vacuum pressureless sintering is too low, the sintering effect is not good, and the density and thermal conductivity of the black alumina ceramic material will decrease significantly.
[0070] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the black alumina ceramic material of the present invention, the holding time of vacuum pressureless sintering will affect its performance. When the holding time of vacuum pressureless sintering is controlled at 4 to 6 hours, the performance of the obtained black alumina ceramic material is better. If the holding time is too long, the density and thermal conductivity of the black alumina ceramic material will not be significantly improved, but energy waste will be caused. If the holding time is too short and the sintering degree is insufficient, the density of the black alumina ceramic material is insufficient and the thermal conductivity is also greatly reduced.
[0071] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention adopts a vacuum pressureless sintering method to sinter the sample under low pressure, thereby inhibiting the growth of grain size, effectively exhausting the gas in the body, and improving the density and thermal conductivity of the black alumina ceramic.
[0072] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a black alumina ceramic material, characterized in that: The preparation method comprises the following steps: (1) mixing aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide, chromium oxide and a solvent to obtain an aluminum oxide ceramic mixed solution; (2) mixing the alumina ceramic mixed liquid with a binder, and grinding to obtain an alumina ceramic powder; (3) The alumina ceramic powder is subjected to cold pressing treatment and then to vacuum pressureless sintering treatment to obtain the black alumina ceramic material.
2. The preparation method according to claim 1, characterized in that The mass ratio of aluminum oxide, magnesium oxide, silicon dioxide, iron oxide, manganese oxide and chromium oxide in step (1) is (85-90):(0.5-2):(2-4):(2-4):(2-5):(5-10); Preferably, the solvent in step (1) comprises water.
3. The preparation method according to claim 1 or 2, characterized in that: The mixing in step (1) comprises pre-mixing magnesium oxide, silicon dioxide, iron oxide, manganese oxide, chromium oxide and a solvent in one step, and then adding aluminum oxide for two-step mixing; Preferably, the one-step mixing time is 2h to 4h; Preferably, the two-step mixing time is 10h to 20h; Preferably, the solid content of the alumina ceramic mixed solution in step (1) is 50% to 60%.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The binder in step (2) comprises a polyvinyl alcohol aqueous solution; Preferably, the mass concentration of the polyvinyl alcohol aqueous solution is 3% to 8%; Preferably, the mass ratio of the solute in the polyvinyl alcohol aqueous solution to the solid material in the alumina ceramic mixed solution is (0.2-1):
100.
5. The preparation method according to any one of claims 1 to 4, characterized in that: After the grinding treatment in step (3), the obtained material is introduced into an aluminum pan for drying.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The pressure of the cold pressing treatment in step (3) is 150MPa to 300MPa; Preferably, the holding time of the cold pressing treatment in step (3) is 2 min to 5 min.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The cold pressing treatment in step (3) is followed by a degreasing treatment.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The vacuum degree of the vacuum pressureless sintering process in step (3) is ≤3×10 -3 Pa; Preferably, the heating rate of the vacuum pressureless sintering process in step (3) is 0.5°C / min to 2°C / min; Preferably, the temperature of the vacuum pressureless sintering treatment in step (3) is 1500° C. to 1600° C.; Preferably, the holding time of the vacuum pressureless sintering treatment in step (3) is 4 h to 6 h.
9. A black alumina ceramic material, characterized in that: The black alumina ceramic material is prepared by the preparation method according to any one of claims 1-8.
10. An application of the black alumina ceramic material as claimed in claim 9, characterized in that: The black alumina ceramic material is used for semiconductor devices.
Citation Information
Patent Citations
Black aluminum oxide with high ceramic properties and method for preparing black aluminum oxide
CN107954698A
Black aluminum oxide ceramic and preparation method thereof
CN117843350A
Low temperature sintered alumina black ceramic, and preparation method thereof
CN110330315A
Tape casting preparation method of aluminum oxide ceramic chip for electrostatic chuck
CN118495928A
Cited By
Method for reducing chromatic aberration of alumina ceramics
CN121135382A